2002
DOI: 10.1182/blood.v100.6.2005.h81802002005_2005_2011
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of human herpesvirus 6 infection with a high viral load in cord blood stem cell transplant recipients

Abstract: Human herpesvirus 6 (HHV-6) infection in recipients of cord blood stem cell transplants (CBSCTs) was estimated by semiquantitative and real-time quantitative polymerase chain reaction (PCR) and reverse-transcription PCR. Of the CBSCT recipients, 7 (70%) of 10 had active HHV-6 infection after transplantation, and all 7 were inferred from their age to have already had a primary infection. Because HHV-6 DNA is seldom detected in cord blood, these cases were considered likely to represent reactivation. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
1
30
1
3
Order By: Relevance
“…We also demonstrated that CBT was a significant risk of HHV‐6 encephalitis/myelitis in this study. This may be associated with the absence of primed HHV‐6‐specific memory T cells and the immunologic immaturity of CBT . Yoshihara et al .…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that CBT was a significant risk of HHV‐6 encephalitis/myelitis in this study. This may be associated with the absence of primed HHV‐6‐specific memory T cells and the immunologic immaturity of CBT . Yoshihara et al .…”
Section: Discussionmentioning
confidence: 99%
“…These factors include immunosuppressive agents, chemotherapeutic or antibiotic agents, systematic use of G‐CSF, and reaction or allergy to blood products. In addition, viral infections, especially human herpesvirus 6 (HHV‐6) reactivation may be associated with fever and rash after CBT (13). Although Patel et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the immunocompetent patient HHV‐6B is the cause of sixth disease (exanthem subitum). HHV‐6 (mainly variant B) infection has also been associated with morbidity post‐haematopoietic stem cell transplant (HSCT), especially delayed platelet and monocyte engraftment (Ljungman et al , 2000), encephalitis (Zerr, 2006) and fever and rash (Sashihara et al , 2002).…”
mentioning
confidence: 99%